Parenting begets parenting: A neurobiological perspective on early adversity and the transmission of parenting styles across generations - Lomanowska, A.M.; Boivin, M.; Hertzman, C.; Fleming, A.S. (Neuroscience, 2017)
•An important predictor of parenting behavior is how parents were parented themselves.•Adverse childhood experiences affect parenting behavior in later-life.•Early adversity affects the psychological and physiological mediators of parenting.•Effects of childhood adversity on parenting may be perpetuated inter-generationally.•Interacting genetic and environmental factors contribute to intergenerational effects. The developing brains of young children are highly sensitive to input from their social environment. Nurturing social experience during this time promotes the acquisition of social and cognitive skills and emotional competencies. However, many young children are confronted with obstacles to healthy development, including poverty, inappropriate care, and violence, and their enhanced sensitivity to the social environment means that they are highly susceptible to these adverse childhood experiences. One source of social adversity in early life can stem from parenting that is harsh, inconsistent, non-sensitive or hostile. Parenting is considered to be the cornerstone of early socio-emotional development and an adverse parenting style is associated with adjustment problems and a higher risk of developing mood and behavioral disorders. Importantly, there is a growing literature showing that an important predictor of parenting behavior is how parents, especially mothers, were parented themselves. In this review, we examine how adversity in early-life affects mothering behavior in later-life and how these effects may be perpetuated inter-generationally. Relying on studies in humans and animal models, we consider evidence for the intergenerational transmission of mothering styles. We then describe the psychological underpinnings of mothering, including responsiveness to young, executive function and affect, as well as the physiological mediators of mothering behavior, including hormones, brain regions and neurotransmitters, and we consider how development in these relevant domains may be affected by adversity experienced in early life. Finally, we explore how genes and early experience interact to predict mothering behavior, including the involvement of epigenetic mechanisms. Understanding how adverse parenting begets adverse parenting in the next generation is critical for designing interventions aimed at preventing this intergenerational cycle of early adversity.